2020
DOI: 10.7812/tpp/19.154
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Care for Those in Need—Today: Collaborating to Solve the Uninsured Crisis in America

Abstract: This retrospective, observational cohort study of mechanically ventilated patients at 21 community and 2 academic hospitals demonstrated that in 28,758 derivation cohort admissions, every 10% increase in SpO2/ FiO2 time at risk (SF-TAR) was associated with a 24% increase in adjusted odds of hospital mortality. The SF-TAR can identify ventilated patients at increased risk of death, offering modest improvements compared with single SpO2/FiO2 and P/F ratios. This longitudinal, noninvasive, and broadly generalizab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…These programs can serve as potential avenues for addressing health care disparities. 99 Providers can also advocate for robust metrics and transparency regarding outcomes at the population and community level. This transparency creates accountability within the health care system, driving continuous improvement and ensuring that providers deliver meaningful care to their patients.…”
Section: Theme Analysismentioning
confidence: 99%
“…These programs can serve as potential avenues for addressing health care disparities. 99 Providers can also advocate for robust metrics and transparency regarding outcomes at the population and community level. This transparency creates accountability within the health care system, driving continuous improvement and ensuring that providers deliver meaningful care to their patients.…”
Section: Theme Analysismentioning
confidence: 99%
“…4 Another strategy based on voluntarism is to provide care via physician volunteers. 5 According to the National Association of Free and Charitable Clinics (NAFC), in 2022, physician volunteers helped 1.7 million patients through 5.8 million patient visits. 5 Importantly, the majority of the patients at these charitable clinics are employed.…”
mentioning
confidence: 99%
“…5 According to the National Association of Free and Charitable Clinics (NAFC), in 2022, physician volunteers helped 1.7 million patients through 5.8 million patient visits. 5 Importantly, the majority of the patients at these charitable clinics are employed. 6 One study showed that 34% had full-time employment but no benefits.…”
mentioning
confidence: 99%